Evaluation of efficacy of a bioresorbable membrane in the treatment of oral lichen planus - Anoop Kapoor; Poonam Sikri; Vishakha Grover; Ranjan Malhotra; Sonia Sachdeva (Wolters Kluwer Medknow Publications, 2014)
Background: Gingival involvement is commonly seen in lichen planus, a chronic mucocutaneous inflammatory condition of the stratified squamous epithelia. It is often painful and may undergo malignant transformation and thus warrants early diagnosis and prompt treatment. The aim of this study is to evaluate the use of a bioresorbable membrane (Polyglactin 910) in the management of erosive lichen planus of gingiva. Materials and Methods: A split-mouth randomized controlled trial was carried out. Fifteen patients with identical bilateral lesions of lichen planus on gingiva were included in the study. Three parameters were selected for the clinical assessment of gingival lesions: Surface texture, color, and burning sensation. After complete oral prophylaxis, an excisional biopsy procedure was carried out for lesions on both sides, but on the experimental side, the biopsy procedure was combined with placement of the bioresorbable membrane. The statistical significance of intergroup differences in measurements was tested by using an independent sample t-test. A two-tailed P-value less than 0.05 was considered as statistically significant. Results: Intragroup comparisons revealed a statistically significant difference between mean value of grades at 6, 12, and 24 weeks in both groups for the surface texture, color, and burning sensation of gingiva, respectively. For intergroup comparison of change in surface texture, color, and burning sensation of gingiva between group A and group B, differences were statistically nonsignificant. Conclusion: Surgical management of the lesion accomplished significant improvement of lesion with no significant additional clinical benefits with the application of bioresorbable membrane. Worsening of baseline scores was not observed in any case at the end of the study.